The Influence of Social Media Marketing, Service Quality, and Ease of Transactionson Purchase Decisions - Putri Azijah Pasaribu; Muhamad Prastyo Hadi; Theresia Putri Charabita (Yayasan Az Zukhruf Cendikia, 2025)
Objective – This study aims to find out and analyze the influence of social media marketing, service quality and ease of transactions on purchase decisions. Design/methodology/approach – This study uses a quantitative type of research. This research was conducted using a questionnaire distributed to consumers of Sea Makeup products, namely 110 questionnaires shared through social media. Each questionnaire distributed has 51 questions to be answered by respondents. Of the 110 questionnaires distributed, 66 respondents gave answers. To get the results of this study, the researcher used SmartPLS 3. Findings – The results of this study determine that social media marketing has a positive effect and has a significant effect on purchase decisions, ease of transactions has a positive effect and has a significant effect on purchase decisions. Limitations of the Research – The limitations of this study are all variables, namely social media marketing variables, service quality, ease of transactions as independent variables, purchase decisions as dependent variables, so that the data obtained is the perception of the respondents. Respondents were obtained through WhatsApp and Instagram so that the filling out of the questionnaire obtained was not guided in filling it out. Some respondents may be reluctant to give honest answers and not all respondents have the same understanding of the questions asked, which can lead to irrelevant or inappropriate answers.